Mortality and missed opportunities along the pathway of care for ST-elevation myocardial infarction: a national cohort study. Issue 3 (June 2015) - Simms, AD; Weston, CF; West, RM; Hall, AS; Batin, PD; Timmis, A; Hemingway, H; Fox, KAA; Gale, CP
Aims: To examine the association between cumulative missed opportunities for care (CMOC) and mortality in patients with ST-elevation myocardial infarction (STEMI). Methods: A cohort study of 112, 286 STEMI patients discharged from hospital alive between January 2007 and December 2010, using data from the Myocardial Ischaemia National Audit Project (MINAP). A CMOC score was calculated for each patient and included: pre-hospital ECG, acute use of aspirin, timely reperfusion, prescription at hospital discharge of aspirin, thienopyridine inhibitor, ACE-inhibitor (or equivalent), HMG-CoA reductase inhibitor and β-blocker, and referral for cardiac rehabilitation. Mixed-effects logistic regression models evaluated the effect of CMOC on risk-adjusted 30-day and 1-year mortality (RAMR). Results: 44.5% of patients were ineligible for ≥1 care component. Of patients eligible for all nine components, 50.6% missed ≥1 opportunity. Pre-hospital ECG and timely reperfusion were most frequently missed, predicting further missed care at discharge (pre-hospital ECG incident rate ratio [95% CI]: 1.64 [1.58–1.70]; timely reperfusion 9.94 [9.51–10.40]). Patients ineligible for care had higher RAMR than those eligible for care (30-days: 1.7% vs. 1.1%; 1-year: 8.6% vs. 5.2%), whilst those with no missed care had lower mortality than patients with ≥4 CMOC (30-days: 0.5% vs. 5.4%, adjusted OR (aOR) per CMOC group 1.22, 95% CI: 1.05–1.42; 1-year: 3.2% vs. 22.8%, aOR 1.23, 1.13–1.34). Conclusions: Opportunities for care in STEMI are commonly missed and significantly associated with early and later mortality. Thus, outcomes after STEMI may be improved by greater attention to missed opportunities to eligible care.